KARAKTERISTIK PERUSAHAAN DAN CREDIT RISK - Permanasari, Erma Wahdani; Suhardjanto, Djoko (JURNAL AKUNTANSI DAN AUDITING, 2014)
The purpose of this study is to determine the effect of characteristic of firm to the level of creditrisk. Characteristics of the firm is proxied by size, leverage, spread ownership, net profit margin,return on equity, industry type and scope of the company’s operations. Measurement of level creditrisk uses PT Pefindo bond rating. Annual reports of listed companies in PT Pefindo and IndonesiaStock Exchange (IDX) 2010-2011 are collected based on purposive sampling techniques. Thepopulation is 238 companies. Sample used amounted to 84 companies. The analysis model usedin this study is multiple linear regression. Results of this study indicate that the level of corporatecredit risk in Indonesia is high because it is below the 50.00%. The test result of multiple regressionshowed that firm of characteristic affect the level of credit risk. Firm characteristics that affectthe level of credit risk are size, leverage, dispersion of ownership, net profit margin and returnon equity.